SISTEM PENILAIAN KINERJA SDM PENDIDIKAN DI SMP YPPI ARRAHMAH (Program Studi Manajemen Pendidikan Islam, 2023)
Performance assessment of educational human resources (HR) is a crucial component in improving the quality of learning and teacher professionalism, especially in Islamic social schools such as SMP YPPI Arrahmah. This study aims to examine the implementation of the performance assessment system at SMP YPPI Arrahmah, analyze its effectiveness, and identify the challenges faced during its implementation. This research employed a descriptive qualitative method using observation and semi-structured interviews with the principal, vice principal, and teachers. The results showed that the performance assessment system at this school is structured, participatory, and emphasizes strengthening Islamic character. Feedback is provided regularly and in a humanistic manner, encouraging increased motivation and teacher performance. However, a high administrative burden remains the main challenge that may disrupt teachers' focus on teaching activities. This study recommends system digitalization and strengthening coaching forums as strategic steps to support teachers' psychological well-being and performance effectiveness